MODERNIZING ZAKAT,INFAK AND SHADAQAH GOVERNANCE: INSIGHTS FROM DIFFUSION,INSTITUTIONAL, AND CONTINGENCY THEORIES - Suwito, Suwito; Kamal, Muhammad; AR Mahdi, Suriana; Sharma, Mala (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the modernization of ZIS governance in Ternate City Indonesia, focusing on Baitul Maal Hidayatullah (BMH) as a case study. The primary aim is to formulate innovative models and strategies that integrate technological solutions with community-based approaches to enhance the effectiveness of zakat management. Adopting a qualitative phenomenological method, the research draws on in-depth interviews with zakat managers and stakeholders involved in digital transformation initiatives. Findings reveal that the application of technology, such as blockchain-based systems, mobile applications, and digital payment platforms, has significantly increased the efficiency, transparency, and accountability of zakat operations. BMH, for instance, achieved 100% of its fundraising target through digital channels, compared to only 50–60% via conventional methods. At the same time, challenges persist, including limited access to technology and low digital literacy in rural areas, prompting the adoption of a hybrid model that combines manual and digital services to maintain inclusivity. The study emphasizes the importance of technology as a driver of modern zakat governance while highlighting the need for adaptive strategies aligned with local socio-cultural contexts. These findings contribute to the broader discourse on Islamic social finance and provide practical insights for enhancing trust, inclusivity, and sustainability in zakat institutions.